The 1st Epistle of Apostle Paul in the Modern Scholarship - Ivanova, Emmanuela (Forum Theologicum Sardicense, 2025)
Emmanuela Ivanova, The 1st Epistle of Apostle Paul to the Corinthians in the Modern Scholarship. The present article provides an overview of contemporary studies on the First Epistle to the Corinthians by Paul the Apostle. It analyzes research from various Christian traditions—Orthodox, Catholic, and Protestant.